Students’ Perception Toward English Tutorial Program Activities and Facilities and Its Influence on Their English Competence - Suryanti Galuh Pravitasari; Elistya Rimawati (Faculty of Language and Literature, University of Surakarta, 2020)
Muhammadiyah University of Surakarta has established its graduate’s quality target as much as ≥ 450 for their English competence measured by standardized TOEIC test. To meet the target, LPIDB as the language center of UMS has provided the students with a kind of speaking activity called English Tutorial Program (ETP). The tutors are active students of at least semester 3 who have got several trainings on conducting the material. This study was aimed at measuring the influence of the students’ perception toward ETP activities and fasilities toward their English ability. The data were collected by giving questionnaires to 200 respondents chosen by using simple random sampling. The data then were analyzed by using multiple linear regression. The result of the study shows that the students’ perception of ETP facilities and activities gave significant influence on their English ability. It was shown by t-value of 4.293 for the perception on facilities and 4.977 for the perception of activities.